Could kyphotic posture disturb body balance in young healthy population? - YILDIZ ÖZER, AYSEL (My University, 2023)
Background: Kyphosis is roughly a slight forward curvature of the spine. A slight kyphosis or posterior curvature is normal throughout the human body and is present in every individual. Hyperkyphotic is a kyphotic angle greater than 40° commonly measured on a lateral X-ray measured by the Cobb method between C7 and T12. Postural instability and loss of balance can result from shifting the center of mass beyond the support base\"s limits. Studies are showing that kyphotic posture affects the center of gravity and affects falls in the elderly, but there are limited studies on the effect of balance in young individuals. Objectives: the correlation between the balance and thoracic kyphosis angle has been investigated. Methods: Forty-three healthy individuals over the age of 18 participated in the study. Participants who met the criteria were split into two groups based on their kyphosis angle. For measuring thoracic kyphosis, Flexi Curve is used. Objective evaluation of static balance was made with NeuroCom Balance Manager® static posturography device. Results: In terms of mean difference, there was no significant difference between the kyphotic and control groups in the balance measures, and there was no correlation between the kyphosis angle and balance measures, according to statistical analysis. Conclusion: According to our study, no significant relationship was found between body balance and thoracic kyphosis in the young population.
Keywords: Tıp; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Physical Medicine and Rehabilitation; Health Sciences; Klinik Tıp (MED); Klinik Tıp; REHABİLİTASYON; ENTEGRE VE TAMAMLAYICI TIP; Clinical Medicine (MED); CLINICAL MEDICINE; REHABILITATION; INTEGRATIVE & COMPLEMENTARY MEDICINE; Tamamlayıcı ve Manuel Terapi; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Rehabilitasyon; Tamamlayıcı ve Alternatif Tıp; Complementary and Manual Therapy; Physical Therapy, Sports Therapy and Rehabilitation; Rehabilitation; Complementary and Alternative Medicine; Balance; Kyphosis; Posture; Thoracic